2021
DOI: 10.1001/jamanetworkopen.2021.28309
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Postinfarction Ventricular Septal Rupture

Abstract: IMPORTANCE Ventricular septal rupture (VSR) is a rare but life-threatening mechanical complication of acute myocardial infarction associated with high mortality despite prompt treatment. Surgery represents the standard of care; however, only small single-center series or national registries are usually available in literature, whereas international multicenter investigations have been poorly carried out, therefore limiting the evidence on this topic. OBJECTIVESTo assess the clinical characteristics and early o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 38 publications
(271 reference statements)
3
45
2
Order By: Relevance
“…Most studies included in our meta-analysis showed no difference in early mortality between CABG and non-CABG groups, while some authors reported a better survival for patients undergoing CABG (6,14,40,54,62). Takahashi et al observed a higher early mortality for patients undergoing cCABG, explaining such results with a more severe CAD and ventricular dysfunction in that group of patients (43).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Most studies included in our meta-analysis showed no difference in early mortality between CABG and non-CABG groups, while some authors reported a better survival for patients undergoing CABG (6,14,40,54,62). Takahashi et al observed a higher early mortality for patients undergoing cCABG, explaining such results with a more severe CAD and ventricular dysfunction in that group of patients (43).…”
mentioning
confidence: 64%
“…When cardiac rupture occurs, it's not always possible to perform PCI nor just coronarography either, thereby precluding any possibility of surgical revascularization (20,24,54). Indeed, most patients with post-AMI mechanical complications are admitted to hospital in poor hemodynamic conditions or even in cardiac arrest, as demonstrated by the 58.2% of subjects developing cardiogenic shock preoperatively and by the 64.3% and 8.6% requiring IABP and ECMO support, respectively (6,18,26,30,41,44).…”
Section: Elbadawi Et Al Recently Analyzedmentioning
confidence: 99%
“… 1 , 3 In fact, while most studies traditionally reported in‐hospital mortality ranging from 20% to 60%, as confirmed by the recently published results from the CAUTION multicenter study, where early mortality among 475 patients was 40.4%, their observed rate of in‐hospital deaths was 26.5%. 4 The series by Belyaev et al has several peculiarities which deserve specific comments and analysis. Indeed, only five patients presented a nonhemodynamically significant postoperative rVSR, with two of them dying during hospitalization, and one patient required emergent reoperation due to hemodynamically relevant rVSR.…”
mentioning
confidence: 99%
“…Despite some studies reporting an rVSR rate as high as 40%, the relatively low incidence of VSR recurrence observed by Belyaev et al is not far from the 12.9% reported in the CAUTION study, where, however, almost half of patients required reoperation, although not impacting on in‐hospital mortality. 4 , 5 , 6 Nevertheless, while all the patients considered for this paper underwent a repair through the “double‐patch frame” technique, in the population considered in the CAUTION study a quite variable set of techniques was adopted. 1 , 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation